Spatial extent of the energetic electron precipitation region during substorms - Bland, Emma; Bozóki, Tamás; Partamies, Noora (Frontiers in Astronomy and Space Sciences, 2022)
The spatial coverage of the energetic electron precipitation (EEP) region during three substorms has been determined using a combination of ground-based instruments in North America. The primary datasets used to determine the presence or absence of EEP are riometer measurements of cosmic noise absorption (CNA); attenuation of the 10-11MHz atmospheric noise in the D-region ionosphere determined using the Super Dual Auroral Radar Netowork (SuperDARN); amplitude variations in subionospheric very low frequency (VLF) propagation observed using the Antarctic-Arctic Radiation-belt (Dynamic) Deposition VLF Atmospheric Research Konsortium (AARDDVARK) VLF receivers, and total electron content measurements derived from global navigation satellite systems. Our results show that substorm EEP during moderate geomagnetic conditions can extend considerably equatorward or poleward of the average latitude limits reported in a previous statistical study of substorm EEP and an EEP model. This evidence is provided by the SuperDARN radars and the radar signature is not always accompanied by cosmic noise absorption measured by the riometers. Further work is required to determine which EEP energies and fluxes the SuperDARN radars are sensitive to, but we can conclude that EEP with sufficient flux to attenuate 10-11MHz radiowaves by ~5dB reaches latitudes well equatorward of the statistical EEP latitude limits previously modelled for >30keV electrons.